Visual disorders caused by cranial arteriovenous fistula with venous drainage into the superior ophthalmic vein - Kondo, Ryushi (Interv Neuroradiol, 2019)
BACKGROUND: Although the abnormal venous drainage into the superior ophthalmic vein (SOV) is a well-known entity responsible for ocular symptoms, it remains unclear to what degree it affects the visual function. The purpose of this study was to evaluate the incidence, characteristics and outcomes of the visual disorders in patients with intracranial arteriovenous fistula (AVF) with venous drainage into the SOV. METHODS: This retrospective study involved eight patients diagnosed with intracranial AVFs with abnormal venous drainage into the SOV between January 2014 and December 2016. RESULTS: The most common location of AVF was the cavernous sinus (CS) in five patients, followed by the intraorbit in two patients and superior sagittal sinus (SSS) in one patient. Visual disorders were detected in three patients (two intraorbit and one CS). The visual field contraction was observed in a patient with intraorbital AVF, and the reduction of visual acuity was confirmed in another patient with intraorbital AVF and a patient with CS dural AVF. All patients underwent an interventional treatment consisting of endovascular embolisation, stereotactic radiosurgery or both, which was selected based on their angioarchitecture. Although angiographic cure of AVF was confirmed in all patients, visual function did not fully recover in two patients with intraorbital AVF. CONCLUSIONS: In cases of intraorbital AVF, visual disorders are more frequent and can result in poorer outcomes compared with other dural AVFs with drainage into the SOV. Early diagnosis and treatment are crucial to preserve the visual function of patients with intraorbital AVF.